2022
DOI: 10.3389/fvets.2022.849856
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Types A and D Involved in Peracute Deaths in Goats Kept in Cholistan Ecosystem During Winter Season

Abstract: Enterotoxemia is a severe and peracute disease caused by Clostridium perfringens (C. perfringens) rendering high mortality leading to huge economic losses, especially in small ruminants. The bacterium induces peracute death in animals based on the rapid production of different lethal toxins. Mortality occurred three private herds of two breeds, i.e., Makhi Cheeni and Beetal, and one non-descriptive (Teddy) herds reared in the desert area of Bahawalpur, Pakistan. At necropsy, tissue samples for histopathology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Studies have indicated that free radicals affect steroidogenesis, apoptosis, lipid peroxidation, and folliculogenesis leading to disorders in embryo preimplantation and infertility in animals [43][44][45]. Therefore, estimation of blood bio-chemistry, oxidative stress, and endogenous antioxidants are considered critical factors in initiating different molecular mechanisms during infectious diseases [46]. Scanty information is available in the published literature regarding the hematological, oxidative stress, and antioxidant profile in brucellosis-infected cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that free radicals affect steroidogenesis, apoptosis, lipid peroxidation, and folliculogenesis leading to disorders in embryo preimplantation and infertility in animals [43][44][45]. Therefore, estimation of blood bio-chemistry, oxidative stress, and endogenous antioxidants are considered critical factors in initiating different molecular mechanisms during infectious diseases [46]. Scanty information is available in the published literature regarding the hematological, oxidative stress, and antioxidant profile in brucellosis-infected cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from other countries have reported a 70% detection rate for C. perfringens netB gene in diseased chicken [ 17 ]. There is much difference in the isolation rate of C. perfringens types across different regions, i.e., there are variations in the prevalence rates of C. perfringens [ 36 ]; likewise, type A is the predominant type in many countries including China, Pakistan etc. [ 29 , 30 , 31 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. perfringens can produce more than ten types of toxins. Among them, alpha toxins and beta toxins can cause damage to the intestinal villus epithelium and endothelial cells, destroy the structural integrity of the cell membrane, and change the permeability of the intestinal wall to induce enteritis; after mucosal damage some toxins are absorbed into the blood circulation and affect other organs distal to the host ( Uzal and McClane, 2011 ; Hussain et al, 2022 ). In past livestock farming, C. perfringens infections were often prevented by adding antibiotics to the feed.…”
Section: Introductionmentioning
confidence: 99%